2015
DOI: 10.1038/srep16071
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the linear flow of fine granules through the addition of elongated particles

Abstract: Sandglasses have been used to record time for thousands of years because of their constant flow rates; however, they now are drawing attention for their substantial scientific importance and extensive industrial applications. The presence of elongated particles in a binary granular system is believed to result in undesired flow because their shape implies a larger resistance to flow. However, our experiments demonstrate that the addition of elongated particles can substantially reduce the flow fluctuation of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…The critical angle of repose of a sandpile consisting of spherical monomer grains was found (Ertaş et al 2002) to increase with the addition of dimers (two spherical particles fused adjacent to each other). However, Guo et al (2015) has observed the 'needle particle effect', where the addition of elongated particles has enhanced the flow of fine granules. They argued that elongated particles played a major role in reducing cohesion and adhesion among fine granules, thus improving the flow conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The critical angle of repose of a sandpile consisting of spherical monomer grains was found (Ertaş et al 2002) to increase with the addition of dimers (two spherical particles fused adjacent to each other). However, Guo et al (2015) has observed the 'needle particle effect', where the addition of elongated particles has enhanced the flow of fine granules. They argued that elongated particles played a major role in reducing cohesion and adhesion among fine granules, thus improving the flow conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, Guo et al. (2015) has observed the ‘needle particle effect’, where the addition of elongated particles has enhanced the flow of fine granules. They argued that elongated particles played a major role in reducing cohesion and adhesion among fine granules, thus improving the flow conditions.…”
Section: Introductionmentioning
confidence: 99%
“…the amount of matter passing through the hopper outlet in a certain amount of time. Contemporary studies use the hopper flow configuration to investigate such complex topics as avalanching [23], self-structuration of the granular fabric triggered by the converging flow [24], shape-induced flow regimes [25], or phase change (i.e. jamming) of the granular sample [26].…”
Section: Introductionmentioning
confidence: 99%